The Price of Fame on X: A Systematic Review of Social and Cultural Consequences of Cyberbullying of Celebrities on X - Motshware, Portia; Francke, Errol; Makwambeni, Blessing (WISE Pendidikan Indonesia, 2025)
This systematic review examines the socio-cultural consequences of cyberbullying targeting celebrities on X, addressing a gap in current research. The increasing prevalence of cyberbullying in the digital era, especially on social media platforms like X, has significant implications for public figures. The review synthesizes findings from 23 peer-reviewed studies published between 2020 and 2025, following the PRISMA framework and employing thematic analysis using Atlas.ti. The research identifies the psychological, personal, and professional impacts of cyberbullying on celebrities, particularly focusing on how the platform's design, including features such as anonymity and rapid information dissemination, exacerbates harmful behaviors. The findings highlight the critical role that X's structure plays in amplifying cyberbullying, with negative consequences such as anxiety, depression, and social isolation for victims. Additionally, the review reveals how celebrities' public personas and constant exposure to online criticism significantly affect their mental health and professional lives. The study also discusses the broader socio-cultural implications, including the normalization of hostility and the public's complex responses to celebrities' victimization. Based on these insights, the review recommends stricter platform regulations and increased support for affected individuals, including the involvement of celebrity managers and healthcare professionals. This research contributes to the understanding of cyberbullying's socio-cultural dynamics on X, offering new perspectives on how digital abuse affects public figures and emphasizing the need for safer online spaces.